A partial recurrence Fibonacci link - ÖZKAN, ENGİN (My University, 2024)
The purpose of this note is to develop a conjecture for a Fibonacci number generating function in terms of the elements of a second-order two parameter partial recurrence relation which arose in an operations research problem on Poisson distributed lead time in inventory control.
Keywords: Matematik; Temel Bilimler; Mathematics; Natural Sciences; Temel Bilimler (Sci); Doğa Bilimleri Genel; Çok Disiplinli Bilimler; Natural Sciences (Sci); Natural Sciences General; Multidisciplinary Sciences; Mantık; Geometri ve Topoloji; Ayrık Matematik ve Kombinatorik; Multidisipliner; Fizik Bilimleri; Logic; Geometry and Topology; Discrete Mathematics and Combinatorics; Multidisciplinary; Physical Sciences; Fibonacci numbers; Lucas numbers; Operations research; Partial recurrence relations